Technical Efficiency of Coal-Fired Power Plants at Electric Power Generation Companies in the Implementation of Biomass Co-Firing - Ni Made Nastiti Saraswati; Dyah Wulan Sari (Cakrawala Repositori IMWI)
The implementation of biomass co-firing in coal-fired power plants has become one of Indonesia’s transitional energy strategies to support carbon emission reduction in the electricity sector. However, the integration of biomass into coal combustion systems may affect operational performance and technical efficiency. This study titled Technical Efficiency of Coal-Fired Power Plants at Electric Power Generation Companies in the Implementation of Biomass Co-Firing aims to analyze the technical efficiency of coal-fired power plants within an electric power generation company before and after the implementation of biomass co-firing using the Stochastic Frontier Analysis (SFA) approach. The study employs monthly panel data from four coal-fired power plant units in Java over the 2017–2024 period. The estimation model applies a translog production function using the one-stage Battese and Coelli (1995) approach. The results indicate that the average technical efficiency of power plants remains relatively high after the implementation of biomass co-firing. The adoption of biomass co-firing has not significantly reduced technical efficiency, as the proportion of biomass in the fuel mix remains relatively low. In addition, plant age and biomass co-firing significantly influence technical inefficiency. These findings suggest that biomass co-firing can serve as a feasible transitional energy strategy without substantially disrupting the operational performance of coal-fired power plants.